2014
DOI: 10.1007/s10120-014-0382-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Western and Japanese criteria for biopsy-based diagnosis of gastric epithelial neoplasia

Abstract: Background In Western countries, gastric cancer (GC) is diagnosed when there is histological evidence of invasion into the lamina propria or beyond the submucosa. In Japan and some other countries, however, diagnosis of GC is based on the degree of structural and cytological abnormality of tumor glands. The aim of the present study was to compare the accuracy of the Western and Japanese criteria for diagnosis of GC. Methods The study included 233 consecutive patients with a postoperative diagnosis of submucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Japanese pathologists diagnose lesions as cancer on the basis of the degree of structural and cytological abnormality of tumor glands, while pathologists in the West make a diagnosis of cancer when there is histological evidence of invasion into the lamina propria or beyond the submucosa. 18 Although the carcinoma in situ of this study was only 6.1%, the pathological difference might affect the incidence. Further studies from Asian countries are required to clarify the trend and the incidence among ethnic groups.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Japanese pathologists diagnose lesions as cancer on the basis of the degree of structural and cytological abnormality of tumor glands, while pathologists in the West make a diagnosis of cancer when there is histological evidence of invasion into the lamina propria or beyond the submucosa. 18 Although the carcinoma in situ of this study was only 6.1%, the pathological difference might affect the incidence. Further studies from Asian countries are required to clarify the trend and the incidence among ethnic groups.…”
Section: Discussionmentioning
confidence: 53%
“…Third, the pathological diagnostic system for gastrointestinal cancers has not been unified between Japan and the Western countries. Japanese pathologists diagnose lesions as cancer on the basis of the degree of structural and cytological abnormality of tumor glands, while pathologists in the West make a diagnosis of cancer when there is histological evidence of invasion into the lamina propria or beyond the submucosa 18 . Although the carcinoma in situ of this study was only 6.1%, the pathological difference might affect the incidence.…”
Section: Discussionmentioning
confidence: 59%
“…In Japan, it has been reported that 87% of new lesions are detected in the early stage [1112], and 81% to 95% of these lesions meet the indications for ESD [45]. However, due to differences in the pathological diagnostic criteria for EGC between Japan and Western countries, EGC in Western countries, especially mucosal cancer, is often followed up as a pre-malignant lesion or pseudo-disease that is not expected to invade into the deeper layer [1013]. This case might represent a milestone in appreciating the importance of ESD for mucosal EGC.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma was distinguished from adenoma based on the following findings: the presence of remarkable variation in nuclear size and shape; presence of hyperchromatic, large, spherical, and vesicular nuclei; irregularly clumped chromatin; increased frequency of mitotic figures; pseudostratified nuclei; poor cellular differentiation; increased nuclear-to-cytoplasmic ratio; loss of nuclear polarity as a nuclear feature; and increased crypt complexity with crowding, branching glandular epithelium, fused glands, budding, a cribriform pattern, and variability of crypt size and shape as structural abnormalities. 17,18 To evaluate the phenotype, immunostaining using antibodies against CD10 (Leica Biosystems, Newcastle upon Tyne, UK; dilution, 1:100), MUC2 (Leica Biosystems; dilution, 1:200), MUC5AC (Leica Biosystems; dilution, 1:200), and MUC6 (Leica Biosystems; dilution, 1:100) was performed. Cytoplasmic reactivity was determined as a positive result for MUC2, MUC5AC, and MUC6 and luminal membranous reactivity as a positive result for CD10.…”
Section: Histological Evaluation and Immunohistochemical Stainingmentioning
confidence: 99%